PENGGUNAAN PERMAINAN KARTU DOMINO SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA NEGERI 9 PEKANBARU - Dermawan, Nita; Copriady, Jimmi; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was about the use of card games or dominoes as chemo-edutainment media. The developed research was applied to improve students learning result on the subject of atomic structure and periodic system of elements in class XI IPA SMAN 9 Pekanbaru. This research is quasi experiment with the randomized control group pretest-posttest design. Technique of taking sample using the cluster random sampling. The used samples were XI IPA2 as experiment class and XI IPA4 as control class, that the class determined randomly after testing normality and homogeneity. The experiment class was given treatment using card games or dominoes as chemo-edutainment media, whilst the control class was not given treatment. The analysis of data was used t-test. The results demonstrated that the data was found tscore > ttable (11,07 > 1,66). This showed that the use of card games or dominoes as chemo-edutainment media could significantly improve the students learning result on the subject of atomic structure and periodic system of elements in class XI IPA SMAN 9 Pekanbaru.Key Words : Card games or dominoes as chemo-edutainment media, Learning Result, atomic structure and periodic system of elements